2019
DOI: 10.1093/jtm/taz049
|View full text |Cite
|
Sign up to set email alerts
|

Patient care without borders: a systematic review of medical and surgical tourism

Abstract: Background Medical tourism (MT) is an increasingly utilized modality for acquiring medical treatment for patients globally. This review assimilates the current literature regarding MT, with particular focus on the applications, ethics and economics. Methods A systematic review of MEDLINE and PubMed Central databases for publications relating to MT from 2005 to 2018 yielded 43 articles for this review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 56 publications
0
39
0
2
Order By: Relevance
“…There is a paucity of authoritative evidence regarding the quality of care and clinical outcomes of procedures performed on orthopedic tourists. A systematic review of surgical tourism by Foley et al reported complication rates as high as 56% including wound infection, poor functional outcome, and adverse cardiovascular events [4]. The risk of importation of antibiotic-resistant bacterial strains associated with inadequate antimicrobial stewardship represents a significant risk to surgical tourists and has public health implications in their home countries [8].…”
Section: Travel Overseas For Orthopedic Carementioning
confidence: 99%
See 2 more Smart Citations
“…There is a paucity of authoritative evidence regarding the quality of care and clinical outcomes of procedures performed on orthopedic tourists. A systematic review of surgical tourism by Foley et al reported complication rates as high as 56% including wound infection, poor functional outcome, and adverse cardiovascular events [4]. The risk of importation of antibiotic-resistant bacterial strains associated with inadequate antimicrobial stewardship represents a significant risk to surgical tourists and has public health implications in their home countries [8].…”
Section: Travel Overseas For Orthopedic Carementioning
confidence: 99%
“…Economic, sociocultural, and technological globalization have facilitated the growth of medical tourism. The motivations of bariatric, cosmetic, transplant, fertility, and stem cell tourists vary, but the greatly reduced costs of procedures performed in developing countries, prohibitive domestic waiting lists, and accessibility of treatment are common driving factors [ 4 ]. The availability of inexpensive flights and the internet have also been instrumental.…”
Section: Travel Overseas For Orthopedic Carementioning
confidence: 99%
See 1 more Smart Citation
“…Urgency to get access is even more important for patients with poor prognosis and those with severe disabilities. With the rise of health globalization, medical tourism is a growing phenomenon, 21 where the objective is not only to get a treatment faster or at a better price but to access what is not available within the domestic system. Systemic issues across health and social care.…”
Section: What Sort Of Financial Help Is Sought In the Uk And Why?mentioning
confidence: 99%
“…5 The prevalence of resistant bacterial strains is higher in mobile populations such as travellers, migrants and refugees, who may be carriers for months after returning home. 6,7 Amongst them are groups of vulnerable people who are disproportionately at risks to COVID-19, putting them at higher risks of complications if they experience secondary bacterial infections. 8 They also carry with them the risks of spreading the resistant bacterial strains to people they would come in contact with during the treatment, such as healthcare workers.…”
mentioning
confidence: 99%